Spontaneous Eruption of Premolar Associated with a Dentigerous Cyst - Irla Karlinne Ferreira de Carvalho; Anibal Henrique Barbosa Luna (Case Reports in Dentistry)
Dentigerous cyst (DC) is the second most common odontogenic cyst with greater incidence in young patients. It presents as a unilocular, asymptomatic radiolucency involving the crown of an impacted tooth, commonly noticed in X-rays to investigate absence, wrong tooth position, or delay in the chronology of eruption. Decompression/marsupialization (D/M) is the most implemented treatment, especially when preserving the tooth involved is advised. The aim of this study is to discuss the DC characteristics that contribute to spontaneous eruption of premolars, by reporting the case of a conservative treatment of DC. This eruption depends on factors such as age, angulation of inclusion, rate of root formation, depth of inclusion, and eruption space. This paper reports the case of a 10-year-old patient with a radiolucent lesion diagnosed as DC involving element 35, which erupted as a result of treatment. The patient was observed during 1 year and 6 months.